Embodied Spatial Learning: Enhancing Design Education Through Experiential Pedagogy and Cognitive Engagement (International Journal of Architecture and Urbanism, 2025)
Understanding space as an embodied and cognitive construct is fundamental in early architectural and interior design (AnID) education. This study introduces a workshop-based pedagogical model aimed at enhancing spatial sensitivity, representation, and imagination among first-year AnID students. Informed by post-pandemic challenges in design learning, the research integrates experiential activities—such as spatial accessibility, proxemic zones, furniture layout, and public space configuration—into an immersive learning framework. A mixed-methods approach involving 45 students utilized pre- and post-surveys alongside in-depth interviews to evaluate affective and cognitive outcomes. The results indicate significant improvements in spatial cognition, design confidence, and student motivation. These findings support a shift from abstract, theory-only models to embodied learning environments, aligning with neuro-architectural discourse on the multisensory nature of spatial perception. The study affirms that integrating cognitive and physical processes within the design curriculum fosters deeper spatial understanding and creative capacity in foundational design education.